2012
DOI: 10.1007/s13365-012-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde axonal transport of VZV: kinetic studies in hESC-derived neurons

Abstract: Retrograde axonal transport of the neurotropic alphaherpesvirus Varicella zoster virus (VZV) from vesicles at the skin results in sensory neuron infection and establishment of latency. Reactivation from latency leads to painful herpes zoster. The lack of a suitable animal model of these processes for the highly human-restricted VZV has resulted in a dearth of knowledge regarding the axonal transport of VZV. We recently demonstrated VZV infection of distal axons, leading to subsequent capsid transport to the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 29 publications
4
40
0
Order By: Relevance
“…These results are similar to quiescent HSV-1 in neurons obtained from adult murine trigeminal ganglia wherein RNA-seq data suggest transcription from multiple regions of the virus genome in addition to LAT (Harkness et al, 2014). As the neurons can be maintained in compartmented microfluidic chambers that orientate neurite outgrowth, infection of axons with fluorescently tagged virus permits direct viewing of retrograde transport to neuronal cell bodies (Markus et al, 2011;Grigoryan et al, 2012). These nearpure (w95 % bIII-tubulin expressing) neuronal cultures provide an excellent opportunity to observe the outcome of VZV infection, such as induction of host anti-apoptotic genes (Markus et al, 2014), although latency (long-term presence of VZV DNA with limited transcription) has not yet been obtained.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VIsupporting
confidence: 68%
“…These results are similar to quiescent HSV-1 in neurons obtained from adult murine trigeminal ganglia wherein RNA-seq data suggest transcription from multiple regions of the virus genome in addition to LAT (Harkness et al, 2014). As the neurons can be maintained in compartmented microfluidic chambers that orientate neurite outgrowth, infection of axons with fluorescently tagged virus permits direct viewing of retrograde transport to neuronal cell bodies (Markus et al, 2011;Grigoryan et al, 2012). These nearpure (w95 % bIII-tubulin expressing) neuronal cultures provide an excellent opportunity to observe the outcome of VZV infection, such as induction of host anti-apoptotic genes (Markus et al, 2014), although latency (long-term presence of VZV DNA with limited transcription) has not yet been obtained.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VIsupporting
confidence: 68%
“…Herpes zoster associated with varicella vaccine is most common at the site of the vaccine inoculation (43), and about 50% of zoster cases associated with vaccination are due to WT virus (50). Also, VZV has previously been shown to enter neurons in vitro from nerve endings by cell-to-cell contact with infected cells or cell-free virus followed by transaxonal transport to the soma (16,17,21).…”
Section: Discussionmentioning
confidence: 99%
“…The use of stem cell-derived neurons contrasts with the use of neurons from sensory or cranial nerve ganglia isolated from human cadavers, most of which have already been infected with VZV. Neurons from hESCs fully support lytic infection after infection with cellassociated POka VZV of either the cell body (soma) or axons through retrograde transport using compartmented microfluidic chambers (16,17). In this model, the cellular transcriptome in…”
mentioning
confidence: 99%
“…ORF7 is non-essential for VZV growth in vitro but has dual roles as virulence determinants in human skin and DRG tissue ex vivo/in vivo (Zhang et al, 2010;Selariu et al, 2012). Recently, several further studies have demonstrated that deletion of ORF7 does not prevent viral entry, viral replication and viral protein expression as well as retrograde transport of virus particles from axon terminals to somata but substantially affects secondary envelopment and cell-to-cell spread of VZV in differentiated neuronal cells in vitro (Grigoryan et al, 2012;Jiang et al, 2017). On the other hand, ORF53 is essential for VZV replication (Zhang et al, 2010), however, its characteristics have remain unstudied to date.…”
Section: Discussionmentioning
confidence: 99%